Radiofrequency therapy in back pain and complex regional pain syndrome (Rheumatology Reports, 2011)
Percutaneous radiofrequency procedures are frequently used in the management of chronic pain. Continuous radiofrequency (CRF) has been established as a safe and effective treatment for pain originating from facet and sacroiliac joints by way of co-agulation of their nerve supply. Different methods have been proposed to account for the complex nerve supply of the sacroiliac joint. Due to its neurodestructive property, CRF was limited to the treatment of neuropathic pain. When applied to the dorsal root ganglion (DRG) for spinal pain or to the sympathetic ganglia in treatment of CRPS, heat related side effects have been reported. With the development of pulsed radiofrequency (PRF), a less destructive alternative to CRF became available, that is more suitable to treat neuropathic pain. PRF was adopted in the treatment of several pain conditions with different success. The results with PRF adjacent to the DRG are promising, whereas for facet and sacroiliac joint pain PRF could not yet be proven equally effective as CRF. As for PRF in CRPS there is almost no evidence available. The potential of PRF seems to lie in those areas where CRF is of limited value. Con-versely, it is questionable if PRF will ever be equally effective in indications, where CRF is already well established. Despite its active use in clinical practice, PRF is not validated yet nor is its mode of action. The literature in both cases is accumulating but further studies are urgently needed.